How Do Pedestrians Perceive The Safety, Comfort, And Usefulness Of A Walking Space? An Exploratory Study of Pedestrian Perception - Marisa, Amanda Rifqa; Fuad, Achmad Hery (UI Scholars Hub, 2023)
Car-oriented development has brought several negative impacts on human quality of life. Therefore, it is necessary to pay more attention to walkability as one of the essential aspects of it, especially in the urban area. In the meantime, most research on walking and walkability still overlooks the role of the pedestrian's perspective in examining walkability. Hence, this research tries to fill the gap in walkability research by exploring the pedestrian perspectives on the safety, comfort, and usefulness of walking space as the three overlapping aspects between walkability and walking needs. This research took context in Suryakencana, Bogor City, Indonesia. To collect information on pedestrian perception and reveal the involved factors, this study used semi-structured-map-based interviews and field observation. By utilizing descriptive analysis, this study highlights the need to consider both physical and non-physical factors to create a safe, comfortable, and useful walking space, and it also found several contributing factors to the perception of safety, comfort, and usefulness of walking space. This research is expected to improve the understanding of walking from the pedestrian perspective and to reconsider the salient factors in developing pedestrian space, hence can accommodate better pedestrians' needs.